Retailing - Dunne, Patrick M.; Lusch, Robert; Gable, Myron ([Cincinnati, Ohio] : South-Western College, 1995)
The book presents Introduction to Retailing, The Retailing Environment, Location Analysis, Managing Retail Operations, and Retail Management.
Keywords: Management; Retail trade; Retail trade